Determinants of Economic Growth: A Review of Local Governments in Sumatera Island - Rahma Putri Yandari; Fitrian Rizky (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study seeks to analyze the impact of health expenditure, education expenditure, capital expenditure, the Human Development Index, and the unemployment rate on economic growth in the local governments of regencies and cities on the island of Sumatera. Economic growth serves as a significant metric for assessing the economic vitality of a nation or region. Factors impacting this may encompass health expenditure, education expenditure, capital expenditure, the Human Development Index, and the unemployment rate. This study's population comprises 154 local governments from regencies and cities on the island of Sumatra. It utilized a saturated sampling strategy and a panel data approach during a four-year observation period, yielding 616 research samples from 2020 to 2023. The employed data analysis technique is panel data regression, with a significance threshold of 5%. The study's findings reveal that health expenditure does not significantly influence economic growth, indicating that health spending has not effectively enhanced labor productivity through improvements in public health. Moreover, educational expenditure positively impacts economic growth, suggesting that education can improve skills and labor productivity, thus augmenting economic production. The study concludes that capital expenditure adversely impacts economic growth, suggesting that it diminishes economic growth despite proper allocation, demonstrating inefficiency and lack of productivity in its execution. The Human Development Index (HDI) does not influence economic growth, indicating that the HDI, which includes factors like education, health, and living standards, has not evolved adequately to impact economic growth. The unemployment rate does not affect economic growth, indicating that labor market conditions and structural variables, such as the alignment of skills and knowledge, may impede economic growth in a region. Not all governmental expenditure or socio-economic metrics yield the anticipated effect on economic growth. The effectiveness of resource distribution, policy emphasis, and the overarching economic environment significantly influence the effects of these diverse elements. Additional investigation may be necessary to comprehend the dynamics behind these findings.